2001
DOI: 10.1212/wnl.57.8.1461
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 and the pattern of regional brain atrophy in Alzheimer’s disease

Abstract: Different patterns of regional brain atrophy were found among patients of different APOE genotypes. The effect of APOE epsilon 4 allele on the brains of AD patients may have regional specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
100
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 42 publications
17
100
1
Order By: Relevance
“…One may assume that sample characteristics, such as age, gender or cognitive status may contribute to discrepancies between studies. However, age, gender and MMSE scores were matched between the AD patients with and without ApoE4 genotype both in our sample and in the previous study showing a significant effect of ApoE4 [19]. Similar to us, one earlier study found no effect of ApoE4 genotype on amygdala volume [30] in AD patients.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…One may assume that sample characteristics, such as age, gender or cognitive status may contribute to discrepancies between studies. However, age, gender and MMSE scores were matched between the AD patients with and without ApoE4 genotype both in our sample and in the previous study showing a significant effect of ApoE4 [19]. Similar to us, one earlier study found no effect of ApoE4 genotype on amygdala volume [30] in AD patients.…”
Section: Discussionsupporting
confidence: 86%
“…This argument does not hold, however, given the subject numbers in this and one previous study [23]. Cohens d in one relatively large positive study comprising 138 patients was 0.55 [19]. Our study was powered to detect an effect size of 0.55 at 80% power and a p value of 0.05 in the AD group.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…One in vivo SPECT study has suggested that delusions in AD may be associated with hypoperfusion in the temporal lobes (Starkstein et al, 1994), and some (Lee et al, 2003) but not all (van Dyck et al, 1998) functional imaging studies have shown that AD patients who carry the e4 allele have reduced temporal lobe function. The structural MRI literature is more unified in showing greater medial temporal lobe atrophy in association with the e4 allele in AD (Lehtovirta et al, 1996b;Hashimoto et al, 2001;Basso et al, in press). …”
Section: Interpretation Of An Increased Risk Of Psychosis In Apoe E4 mentioning
confidence: 99%
“…Among the three major isoforms of ApoE (e2, e3, and e4), the e4 allele has been reported to increase an individual's risk of developing AD, and decrease age of disease onset, in proportion to the number of e4 alleles present (Corder et al, 1993;Farrer et al, 1997). The search for phenotypic correlates of e4 has included neuropathological studies of the rate of b-amyloid (Ab) deposition Nagy et al, 1995;Norrman et al, 1995;Gomez-Isla et al, 1996), neurofibrillary tangle formation Nagy et al, 1995;Norrman et al, 1995;Gomez-Isla et al, 1996), cholinergic markers (Poirier et al, 1995;Soininen et al, 1995), and medial temporal lobe atrophy (Lehtovirta et al, 1996b;Hashimoto et al, 2001;Basso et al, in press).…”
Section: Introductionmentioning
confidence: 99%